Borylative cyclisation of diynes using BCl3 and borocations. Issue 22 (23rd May 2019) - Warner, Andrew J.; Enright, Kieron M.; Cole, John M.; Yuan, Kang; McGough, John S.; Ingleson, Michael J.
Abstract : Products from the borylative cyclisation of diynes using BCl3 is dependent on substituent effects, however, some control of product outcome is achieved using borocations or BCl3 in the presence of [BCl4 ] − . Abstract : The borylative cyclisation of 1, 2-dialkynyl benzenes with BCl3 leads to dibenzopentalenes ( via intramolecular SE Ar) or benzofulvenes ( via chloride addition) depending on substituents, with stabilised vinyl cation intermediates ( e.g. with a p -MeO-C6 H4 -group) favouring the latter. The use of borocations leads to more selective dibenzopentalene formation, while other diyne frameworks undergo intramolecular SE Ar selectively even with p -MeO groups.